Automatically accounting for physical activity in insulin dosing for type 1 diabetes. (December 2020) - Ozaslan, Basak; Patek, Stephen D.; Fabris, Chiara; Breton, Marc D.
Highlights: Step-count data from wearable physical activity trackers is leveraged to track and quantify daily physical activity. An approach to calculate the accumulated glycemic impact from prior physical activity is presented. A physical activity informed mealtime insulin bolus calculator is developed. Simulation results suggest that the proposed physical activity informed insulin dosing could result in significantly improved postprandial glucose control in individuals with type 1 diabetes, compared with the standard dosing. Abstract: Background and Objective: Type 1 diabetes is a disease characterized by lifelong insulin administration to compensate for the autoimmune destruction of insulin-producing pancreatic beta-cells. Optimal insulin dosing presents a challenge for individuals with type 1 diabetes, as the amount of insulin needed for optimal blood glucose control depends on each subject's varying needs. In this context, physical activity represents one of the main factors altering insulin requirements and complicating treatment decisions. This work aims to develop and test in simulation a data-driven method to automatically incorporate physical activity into daily treatment decisions to optimize mealtime glycemic control in individuals with type 1 diabetes. Methods: We leveraged glucose, insulin, meal and physical activity data collected from twenty-three individuals to develop a method that (i) tracks and quantifies the accumulated glycemic impact from daily physical activity in real-time, (ii) extracts an individualized routine physical activity profile, and (iii) adjusts insulin doses according to the prolonged changes in insulin needs due to deviations in daily physical activity in a personalized manner. We used the data replay simulation framework developed at the University of Virginia to "re-simulate" the clinical data and estimate the performances of the new decision support system for physical activity informed insulin dosing against standard insulin dosing. The paired t -test is used to compare the performances of dosing methods with p < 0.05 as the significance threshold. Results: Simulation results show that, compared with standard dosing, the proposed physical-activity informed insulin dosing could result in significantly less time spent in hypoglycemia (15.3± 8% vs. 11.1± 4%, p = 0.007) and higher time spent in the target glycemic range (66.1± 11.7% vs. 69.6± 12.2%, p < 0.01) and no significant difference in the time spent above the target range(26.6± 1.4 vs. 27.4± 0.1, p = 0.5). Conclusions: Integrating daily physical activity, as measured by the step count, into insulin dose calculations has the potential to improve blood glucose control in daily life with type 1 diabetes.